Indian Englis [ - Sailaja, P. [ (Pingali)] , 1962- (Dialects of English, 2009)
Offers a descriptive account of English as it is used in India. This book includes: a discussion of the sociolinguistic and cultural factors; the history of the establishment of English in India, bringing it up to modern times; and, a description of the linguistic aspects - phonetics and phonology, lexical, discourse and morphosyntactic features